Measurement of Force Impact Taekwondo Athletes, Assessing the Possibility of Injury of Human Head. (2016) - Svoboda, Martin; Soukup, Josef; Jelen, Karel; Kubový, Petr
Abstract: The article presents the results of measurements impact taekwondo athletes to the board which opens after hitting stroke. Measured values are compared with the results of scientific studies that dealt with human head injuries due to the impacts of various kinds. Most often, these results were determined using cadavers bodies. Force action of the athletes on board was realized by direct punches which are combat sport led to facial parts of opponent. In their own measurement was determined time course of forces impinging on the dynamometer plate including size and direction of the force. Dynamometer measured forces to 10000 N. The frequency was set to 1000 Hz. Estimate of accuracy was 0.5% of measured value. A composite plate was attached to a dynamometer using special steel structures. When comparing the results was found that the combat sport of taekwondo strikes, including other power effects (eg. others combat sports, falls, blows to the head in accidents, etc.) can cause fractures of the facial bones and even other human head trauma or cervical vertebrae.